The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/braincomms/fcab036
|View full text |Cite
|
Sign up to set email alerts
|

A novel remitting leukodystrophy associated with a variant in FBP2

Abstract: Leukodystrophies are genetic disorders of cerebral white matter that almost exclusively have a progressive disease course. We became aware of three members of a family with a disorder characterized by a sudden loss of all previously acquired abilities around one year of age followed by almost complete recovery within two years. Cerebral MRI and myelin sensitive imaging showed a pronounced demyelination that progressed for several months despite signs of clinical improvement and was followed by remyelination. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Previously, we have shown that in the cell culture, fibroblasts-to-cardiomyocytes crosstalk induced transitions that mimicked the postnatal shift from the "fetal" to "mature" mode of cardiac myocytes functioning. This included the translocation of FBP2 from the cardiomyocyte nucleus to cytoplasm where, as the dimer and/or the active R-state tetramer, it bound to mitochondrial proteins, including VDAC, and participated in the protection of the mitochondrial membrane [1,3,[9][10][11]16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we have shown that in the cell culture, fibroblasts-to-cardiomyocytes crosstalk induced transitions that mimicked the postnatal shift from the "fetal" to "mature" mode of cardiac myocytes functioning. This included the translocation of FBP2 from the cardiomyocyte nucleus to cytoplasm where, as the dimer and/or the active R-state tetramer, it bound to mitochondrial proteins, including VDAC, and participated in the protection of the mitochondrial membrane [1,3,[9][10][11]16].…”
Section: Discussionmentioning
confidence: 99%
“…To test the FBP2-mitochondria co-localization, murine anti-FBP2 antibody [13], rabbit anti-TOMM antibody (HPA011562; Merck, Darmstadt, Germany) and appropriate secondary antibodies Alexa 633-or FITCconjugated (ThermoFisher Scientific or Merck, respectively) were used. For the analysis of FBP2 co-localization with mitochondria and microtubules with mitochondria, the Manders' coefficient (M) was determined using the JACoP plugin of the ImageJ/FIJI as we described before [11]. The coefficient varies from 0 (no co-localization) to 1 (100% of co-localization).…”
Section: Immunofluorescencementioning
confidence: 99%
See 3 more Smart Citations